Management Analysis of Inclusive Education Services in Inclusive Elementary Schools - Aishah; Udin Syaefudin Sa’ud; Danny Meirawan; Diding Nurdin (Didaktika: Jurnal Kependidikan, 2024)
Inclusive education as a new construction in the educational context both on an international and national scale. Inclusive education aims to provide the best service for general students and students with special needs by providing adequate access and support. School principals as school managers, teachers and school human resources have a very vital role in carrying out their management to improve the quality of education and services in an inclusive manner. An inclusive approach to education aims to provide equal learning opportunities for all children, regardless of their background, abilities or special needs. This research aims to analyze, understand, interpret and discover new theories and practices in quality management of inclusive education services, to create quality services that can be implemented by schools at the elementary school (SD) level in the city of Banda Aceh. This researcher uses qualitative methods with a case study design . The location of this research is at SD Negeri 25 Banda Aceh City. Data collection techniques are interviews, observation, and documentation, then the analysis techniques used are data reduction, data presentation, and drawing conclusions.